Pilot-Scale Anaerobic Digestion of Pig Manure with Thermal Pretreatment: Stability Monitoring to Improve the Potential for Obtaining Methane (2022)
Monitoring and controlling stability in anaerobic digestion (AD) systems are essential, since it allows to obtain information that helps to take corrective actions in case of deviations in the system and to guarantee a stable performance in the biogas production. In this work, a pilot-scale CSRT reactor (1 m3) was monitored during the anaerobic digestion of pig manure with thermal pretreatment (80 C) operated at thermophilic temperature (45 C). The ratio of the volatile organic acids (FOS) to the total inorganic carbonate (TAC) and the pH were the indicators used during the monitoring process to identify deviations in the AD system. Additionally, alkaline solution NaOH (98%) was applied to counteract pH deviations and maintain stability. Chemical oxygen demand (COD) and biogas composition were measured during the AD process. It was found that during the AD process, the FOS/TAC was between the range of 0.5 and 1. The results revealed that, in the anaerobic digestion of pig manure with thermal pretreatment, the pH was kept stable in the range of 6.7–7.4 since no medium acidification occurred. Additionally, the tendency of the chemical oxygen demand decreased from the 10th day of operation, product of the favorable enzymatic activity of the microorganisms, reflected in the stable production of biogas (69% CH4). Finally, it is concluded that thermophilic AD of pig manure with thermal pretreatment is a good option when it is carried out efficiently by employing an adequate energetic integration.